Hepatoprotective cocrystals of isoniazid: synthesis, solid state characterization, and hepatotoxicity studies - Yadav, Balvant; Gunnam, Anilkumar; Thipparaboina, Rajesh; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2019)
Isoniazid (INH) is one of the first line drugs used in combination with pyrazinamide and rifampicin for the management of tuberculosis. Idiosyncratic hepatotoxicity is one of the most common side effects of antitubercular therapy worldwide. The current study explores solid phase modification of INH by cocrystallization with various hepatoprotective coformers, namely chrysin, hesperetin, silibinin, syringic acid (SYRA), and quercetin (QUE) to address hepatotoxicity concerns. Cocrystals were obtained with SYRA and QUE. Supramolecular synthons based on pyridine-carboxyl and pyridine-hydroxyl synthon enabled the formation of cocrystals. INHSYRA and INHQUE cocrystals were characterized by FT-IR, DSC, and PXRD. Single crystal X-ray analysis of INHSYRA revealed that it crystallized in triclinic system with the P (1) over bar space group. Intrinsic dissolution rate studies (IDR) showed slow drug release from both the cocrystals. Hepatoprotective effects of INHSYRA and INHQUE cocrystals were evaluated by a single toxic dose study and a subchronic study for 28 days. Results from the subchronic study indicated significant increase in ALT, AST, and ALP enzyme levels in the INH-treated group whereas the enzyme levels in INHSYRA and INHQUE cocrystal treated group were comparable to that of the untreated group. This study demonstrates the in vivo hepatoprotective effects of coformers SYRA and QUE provide promising evidence for utility of nutraceutical based coformers, to tackle hepatotoxicity associated with various drugs.

High-solubility salts of the multiple sclerosis drug teriflunomide - Gunnam, Anilkumar; Nangia, Ashwini K. (Crystal Growth & Design, 2019)
Teriflunomide (TFM) is an immunomodulatory prodrug of leflunomide which is used for the treatment of multiple sclerosis (MS). It is a Biopharmaceutics Classification System Class (BCS) II drug with low solubility and high permeability. The X-ray crystal structure of TFM is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, and N-H center dot center dot center dot N interactions. In order to study the solubility and dissolution changes of this drug, five multicomponent crystal forms were prepared with amine and amide generally regarded as safe (GRAS) coformers to improve the physicochemical properties such as solubility, dissolution, diffusion, and phase stability. Equimolar TFM-coformer 1:1 salts were crystallized, except for cytosine which afforded a salt cocrystal toluene solvate TFM-CYT-TOL in a 1:2:1 ratio. The multicomponent forms were crystallized by slow solvent evaporation and characterized by single crystal X-ray diffraction. TFM and coformer are bonded by N+-H center dot center dot center dot O-, N-H center dot center dot center dot O, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, N-H center dot center dot center dot N, and C-H center dot center dot center dot F interactions. The bulk phase purity of the salts was characterized by powder X-ray diffraction and infrared and thermal techniques. Solubility, dissolution, and diffusion experiments in pH 7.0 buffer exhibited a significant improvement compared to the reference drug. The morphology and particle size of salts by field emission scanning electron microscopy were related to dissolution behavior. The highest solubility, dissolution, and diffusion profile were observed for TFM-MEA and TFM-TEA salts (monoethanol amine and triethanol amine).